Landslide risk management using geospatial technique: Comparative insights of China and Indonesia - Ermanto, Yakin (ASEAN Natural Disaster Mitigation and Education Journal, 2024)
Landslides are defined as the movement of soil and rocks that form slopes. Landslides can cause environmental damage, property losses, and deaths for people in disaster-prone areas. This study aims to review and compare landslide risk management patterns in China and Indonesia from research conducted in 2019-2023. The method used in this study is a Systematic Literature Review (SLR). While searching for literature using Scopus, Mendeley has a publication period of 2019-2023. The research findings show that disaster risk management also focuses on more than community knowledge in disaster emergency response. However, other elements need attention, namely road sections most vulnerable to landslides, slope conditions, river density, land use, GIS, resources, community participation, and training. In Fengjie County, China, landslide vulnerability is a significant problem, with about 70% of areas in the vulnerability zone very high. In Pengasih Sentolo district, Indonesia, nine villages are included in the very high-risk site, showing significant landslide vulnerability. The integration and application of GIS technology have greatly assisted in assessing landslide susceptibility and identifying high-risk zones. Conclusion: The case study in Fengjie County, China and the study in Pengasih Sentolo District, Kulon Progo, Indonesia, emphasize the importance of using geospatial techniques, particularly GIS, for landslide risk assessment.